Pore morphology reveals interaction of biological and physical processes for structure formation in soils of the semiarid Argentinean Pampa - Fernandez, Romina; Frasier, Ileana; Quiroga, Alberto Raul; Noellemeyer, Elke (Elsevier, 2019)
In order to obtain baseline values for the evaluation of soil degradation, the biological and physical quality of petrocalcic Paleustolls, of the calcrete plains of the Semiarid Region Pampa of Argentina, soils under agricultural (Ag) and native vegetation (NV) were selected, with the same clay content, in which three depth layers (upper, middle and lower) were sampled. Total organic carbon and its fractions, total nitrogen, soil texture, aggregate size distribution, mean weight diameter, aggregate volumetric weight, maximum bulk density, susceptibility to compaction, critical moisture content, hydraulic conductivity, infiltration, penetration resistance were determined. In addition, the size, distribution and shape of the macropores were measured through image analysis of thin sections. As biological indicators, respiration, microbial biomass carbon and nitrogen were determined. Soils under Ag use had lower carbon and nitrogen content, they also had lower total porosity and macroporosity compared to the NV soils, and the predominant shape of macropores was round. This change in the distribution and shape of the pores led to lower rates of infiltration and lower hydraulic conductivity, higher bulk density and greater resistance to penetration. The round macropores were found to be negatively correlated with organic carbon, total porosity and macroporosity and positively with indicators associated with compaction (maximum bulk density, susceptibility to compaction and bulk density). Compacted soils with lower total porosity and higher proportion of round macropores presented higher volumetric weight of the aggregates. The Ag soils with lower carbon and nitrogen content also had lower microbial biomass carbon and respiration, compared to the soils under natural vegetation, and the variables associated with compaction were negatively related to biological properties. The suggested minimum set of indicators included organic carbon, total porosity, mean weight diameter, macropores, penetration resistance, aggregates volumetric weight of 2–3-mm, elongated macropores, respiration and microbial biomass carbon. All of them were strongly related to indicators that reflect the physical, chemical and biological functionality of the soil that sustain soil-based ecosystem services. Degradation and rehabilitation processes might be governed by the feedback between pore formation and microbial activity, underpinning the importance of perennial crops and cover crops for providing substrate supply to the soil biota for sustainable agricultural systems.